A study on advance cardiac life support knowledge and skills among health care professionals and their predicting factors during ACLS course - Hamzah, Tengku Mohd Azimin Tengku (2018)
Introduction: Healthcare professionals are expected to have a good updated Advanced Cardiac Life Support (ACLS) knowledge and skills to manage cardiac arrest. Thus, ACLS training course is recognised as the gold standard to provide them with good knowledge and skills. In view of limited data regarding ACLS courses that were organised in Malaysia, this study aimed to determine the level of ACLS knowledge and skill among healthcare professionals and their predicting factors during an ACLS course. Methods: A prospective observational study was conducted in tertiary Hospital Universiti Sains Malaysia, Kelantan (January 2016 till Jun 2017) among healthcare professionals during an ACLS course. A questionnaire regarding candidates’ demographic data and professional backgrounds was collected at the beginning of the course and all pre-course MCQ test, post-course MCQ test and practical CAS-test results were collected and analysed. The association between socio-demographics, professional backgrounds and final course results then were analysed. Results: A total of 123 ACLS course candidates were enrolled in this study. There was a significant difference between pre and post ACLS knowledge among candidates following ACLS course (t-statistic (df): 9.35 (121), p<0.001). The level of ACLS knowledge and skills was good as a majority of 78.9% passed the overall test. On multivariate analysis, there were significant associations between gender (p=0.003), designation (p=0.027) and pre-test result (p=0.002) with the level of knowledge and skill shown by overall test results. Conclusions: Structured ACLS training improved the level of knowledge and skills among healthcare professionals and were significantly associated with gender, pre-course knowledge and professional designation.